2004
DOI: 10.1007/bf03218391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of poly(vinyl alcohol)/alginate hydrogels cross-linked by γ-ray irradiation technique

Abstract: In this work, we prepared hydrogels for wound dressing from a mixture of poly(vinyl alcohol) (PVA) and alginate using the 60 Co γ-ray irradiation technique. We examined the physical properties of these hydrogels, including gelation, water absorptivity, and gel strength, to evaluate the applicability of these hydrogels for wound dressings. The biocompatibility of these hydrogels was also evaluated in vitro, in cultures of mouse fibroblasts, and in vivo, by subcutaneous implantation studies in rats. The gel cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Finally, the hydrogels were taken out from the shaker and dried in oven at 60 °C until a constant weight (W f ). Gel fraction was calculated gravimetrically (Nam et al, 2004) ). Dried hydrogels were soaked in distilled water at room temperature.…”
Section: Gel Fraction Testmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the hydrogels were taken out from the shaker and dried in oven at 60 °C until a constant weight (W f ). Gel fraction was calculated gravimetrically (Nam et al, 2004) ). Dried hydrogels were soaked in distilled water at room temperature.…”
Section: Gel Fraction Testmentioning
confidence: 99%
“…Nam et al (2004) reported that they obtain the gel fraction in the range of 80-95% from the SA-PVA hydrogel. It means that the higher the irradiation dose, the closer the crosslinking formed, hence only a small amount of available substances were water soluble.…”
Section: Effect Of Sa Concentration and Irradiation Dose On Gel Fractionmentioning
confidence: 99%
See 3 more Smart Citations